The efficacy of linked color imaging for the endoscopic diagnosis of mucosal healing in quiescent ulcerative colitis. Issue 9 (26th March 2021) - Takagi, Tomohisa; Uchiyama, Kazuhiko; Kajiwara‐Kubota, Mariko; Kashiwagi, Saori; Toyokawa, Yuki; Hotta, Yuma; Tanaka, Makoto; Inoue, Ken; Dohi, Osamu; Yoshida, Naohisa; Kamada, Kazuhiro; Ishikawa, Takeshi; et al.
Abstract: Background and Aim: The Mayo Endoscopic Subscore (MES) and the Ulcerative Colitis Endoscopic Index of Severity (UCEIS) are used to assess endoscopic mucosal healing in patients suffering from ulcerative colitis. Although mucosal healing is defined by MES 0, relapse of ulcerative colitis is often observed. Over a 48‐month period, this study investigated the efficacy of linked color imaging (LCI) in predicting the long‐term prognosis of ulcerative colitis patients diagnosed with MES 0. Methods: Overall, 26 patients in ulcerative colitis remission, diagnosed with MES 0, were enrolled. Using a LASEREO endoscopic system (Fujifilm Co., Tokyo, Japan), endoscopic colonic images were assessed with linked color imaging and the colitis endoscopic index of severity. Endoscopic LCI images were separated into three subgroups (A, no redness; B, redness with visible vessels; and C, redness without visible vessels). The Geboes score was used to evaluate histology; active mucosa was defined as GS > 2B.1. Results: Linked color imaging classification subdivided colonic mucosa, which had been diagnosed with MES 0, into two classes. The LCI‐A group did not relapse, and the non‐relapse rate was significantly higher ( P  = 0.018) than that in the LCI‐B group. No difference in relapse rates was observed between patients with a colitis endoscopic index of severity of 0 and 1 ( P  = 0.655). There was no statistical difference between the composition of LCI‐A group and the relapse rate between active and inactive mucosa diagnosed by Geboes score. Conclusions: This methodology can be used to evaluate mucosal healing and predict long‐term outcomes in ulcerative colitis patients.